Symptoms of depression in middle-aged and older adults with schizophrenia in Guangzhou, China: a cross-sectional study - Ye, Junrong; Wu, Jialan; Lei, Lingli; Zheng, Dandan; Wei, Yanheng; Liu, Dingjie; Zheng, Xueyu; Li, Jinrong; Ma, Na; Zhang, Yuhan; Chen, Jiao; Guo, Jianxiong; et al. (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to explore the prevalence and risk factors of symptoms of depression in middle-aged and older adults with schizophrenia.MethodsIn this cross-sectional study, 116 participants were recruited from a tertiary psychiatric hospital in Guangzhou, China. The sample consisted of adults aged 40 years and over. Based on their scores on the Geriatric Depression Scale, participants with schizophrenia were categorized into two groups: those with depressive symptoms (scores greater than 10 points) and those without depressive symptoms (scores of 10 points or lower). This study compared the differences in the sociodemographic variables (such as gender, age, education level, marital status, and BMI) and the clinical characteristics (e.g., suicide risk, anxiety level, severity of mental symptoms, insight into illness and treatment attitude, cognitive function, activities of daily living, quality of life, and social support) between two groups. Spearman’s correlation analysis and logistic regression analysis were employed to explore the relevant factors contributing to depression in middle-aged and older adults with schizophrenia.ResultsThe participants had an average age of 63.28 ± 7.87 years, and 88 of the participants (75.9%) are women. Among them, 34 participants (29.31%) exhibited symptoms of depression. Statistically significant differences were observed between the two groups in the affect and resistance sub-dimensions of the Brief Psychiatric Rating Scale (BPRS) and the total scores of the Generalized Anxiety Disorder (GAD) assessment, the Insight and Treatment Attitudes Questionnaire (ITAQ), the Nurses’ Global Assessment of Suicide Risk (NGASR), and the Schizophrenia Quality of Life Scale (SQLS). Furthermore, logistic regression indicated that the resistance sub-dimension of the BPRS (OR = 0.790, 95%CI = 0.648–0.963) and the SQLS (OR = 1.115, 95%CI = 1.055–1.178) and GAD scores (OR = 1.205, 95%CI = 1.029–1.412) are predictive factors for symptoms of depression in individuals with schizophrenia.ConclusionIn middle-aged and older adults with schizophrenia, affective symptoms and quality of life are associated with symptoms of depression.